Effect of copper addition on the thermoelectric power factor and electrical conductivity of As–Se–Sb–Cu thin films. (17th May 2019) - Hegazy, H H; Dahshan, A; Aly, K A
Abstract: Chalcogenides provide features like Seebeck coefficient ( S ), low thermal conductivity coupled with high electrical conductivity; hence they have been identified as one of the best sources for thermoelectric (TE) materials. This research presents an interest in p-type Cu doped As30 Se55 Sb15−x Cux (2.5 ≤ x ≤ 10 at%) films fabricated by thermal evaporation from bulk glasses. Cu addition acts as donors to improve the electron concentration for increasing the electrical conductivity over the entire temperature range significantly. Thermoelectric behavior within the temperature ranges of 300 to 420 K has been studied. Additional electrical properties have also been expounded where, for example, it was observed that the addition of Cu content led to an increase in dc electrical conductivity ( σ ) with a subsequent decrease in activation energy (ΔE). The positive values of the Seebeck coefficient in the entire temperature range indicate p-type semiconductor behavior. As well, from the measured values of S and σ, the carrier concentration ( n ) was obtained. There was a decrease in ΔE attained from the S associated with an increase in the power factor (P) with increasing the Cu content. The power factor ( P ) is seen to be very crucial since it is an essential thermoelectric parameter.